Inquiry & interest-based approaches for learner engagement: instructional perspectives from academic & public libraries - King, Martina; Arnason, Holly (My University, 2017)
Learn how academic and public library staff use inquiry and interest-based structures to engage students, staff, and program participants in learning with technology. Gain an overview of relevant theories and experience these approaches as you get creative with hands-on activities to design a prototype and put on a robot fashion show. Connect techniques with learning outcomes and assessment.
Presented on May 23, 2017 at the WILU conference held at the University of Alberta in Edmonton, Alberta.
Keywords: library instruction; technology; engagement